Evidence of Rickettsia and Orientia Infections among Abattoir Workers in Djibouti - Horton, Katherine C. (Am J Trop Med Hyg, 2016)
Of 49 workers at a Djiboutian abattoir, eight (16%, 95% confidence interval [CI]: 9–29) were seropositive against spotted fever group rickettsiae (SFGR), two (4%, 95% CI: 1–14) against typhus group rickettsiae, and three (6%, 95% CI: 2–17) against orientiae. One worker (9%, 95% CI: 2–38) seroconverted against orientiae during the study period. This is the first evidence of orientiae exposure in the Horn of Africa. SFGR were also identified by polymerase chain reaction in 32 of 189 (11%, 95% CI: 8–15) tick pools from 26 of 72 (36%) cattle. Twenty-five (8%, 95% CI: 6–12) tick pools were positive for Rickettsia africae, the causative agent of African tick-bite fever. Health-care providers in Djibouti should be aware of the possibility of rickettsiae infections among patients, although further research is needed to determine the impact of these infections in the country.